Response to Periodontal Therapy in Diabetics and Smokers - Grossi, Sara G; Skrepcinski, Fred B; DeCaro, Thomas; Zambon, Joseph J; Cummins, Diane; Genco, Robert J (Journal of periodontology (1970), 1996)
Diabetics and smokers are two patient groups at high risk for periodontal disease who also exhibit impaired wound healing and, therefore, constitute two different groups in whom the relationship between host-parasite interaction, outcome of periodontal therapy, and systemic factors is best represented. The results of two independent clinical trials involving treatment of periodontal disease in diabetics and smokers are presented. A new treatment regimen-for the management of periodontal disease associated with diabetes mellitus is proposed. This treatment approach incorporates both antimicrobial agents and pharmacological modulation of the host response. Elimination of periodontal infection and reduction of periodontal inflammation in diabetic patients resulted in a significant short-term reduction in the concentration of glycosylated hemoglobin (HbA ). Control of chronic infections and modulation of the host response offer a new therapeutic approach in the management of patients with both diabetes and periodontal disease. The effect of smoking on periodontal healing is also discussed. The clinical and microbiological response of smokers to non-surgical periodontal therapy is compared to non-smokers. In addition, possible mechanisms whereby diabetes mellitus and cigarette smoking increase the severity of periodontal disease are discussed. J Periodontol 1996;67:1094-1102.